Atmospheric polycyclic aromatic hydrocarbons observed over the North Pacific Ocean and the Arctic area: Spatial distribution and source identification - Xiang Ding; XinMing* Wang; Zhouqing Xie; Caihong Xiang; Bixian Mai; Liguang Sun; Mei* Zheng; Guoying Sheng; Jiamo Fu; Ulrich Pöschl (Atmospheric Environment, 2007)
During the 2003 Chinese Arctic Research Expedition from the Bohai Sea to the high Arctic (37–80°N) aboard the icebreaker Xuelong (Snow Dragon), air samples were collected using a modified high-volume sampler that pulls air through a quartz filter and a polyurethane foam plug (PUF). These filters and PUFs were analyzed for particulate phase and gas phase polycyclic aromatic hydrocarbons (PAHs), respectively, in the North Pacific Ocean and adjacent Arctic region. The ∑PAHs (where ∑=15 compounds) ranged from undetectable level to 4380pgm−3 in the particulate phase and 928–92600pgm−3 in the gas phase, respectively. A decreasing latitudinal trend was observed for gas-phase PAHs, probably resulting from temperature effects, dilution and decomposition processes; particulate-phase PAHs, however, showed poor latitudinal trends, because the effects of temperature, dilution and photochemistry played different roles in different regions from middle-latitude source areas to the high latitudes. The ratios of PAH isomer pairs, either conservative or sensitive to degradation during long-range transport, were employed to interpret sources and chemical aging of PAHs in ocean air. In this present study the fluoranthene/pyrene and indeno[123-cd]pyrene/benzo[ghi]pyrene isomer pairs, whose ratios are conservative to photo-degradation, implies that biomass or coal burning might be the major sources of PAHs observed over the North Pacific Ocean and the Arctic region in the summer. The isomer ratios of 1,7/(1,7+2,6)-DMP (dimethylphenanthrene) and anthracene/phenanthrene, which are sensitive to aging of air masses, not only imply chemical evolving of PAHs over the North Pacific Ocean were different from those over the Arctic, but reveal that PAHs over the Arctic were mainly related to coal burning, and biomass burning might have a larger contribution to the PAHs over the North pacific ocean.
Keywords: Biomass burning